British Military surgical key performance indicators: time for an update?. Issue 5 (17th November 2015) - Marsden, Max ER; Sharrock, AE; Hansen, CL; Newton, NJ; Bowley, DM; Midwinter, M
Abstract : Background: Key performance indicators (KPIs) are metrics that compare actual care against an ideal structure, process or outcome standard. KPIs designed to assess performance in deployed military surgical facilities have previously been published. This study aimed to review the overall performance of surgical trauma care for casualties treated at Role 3 Camp Bastion, Medical Treatment Facility, Afghanistan, in light of the existing Defence Medical Services (DMS) KPIs. The secondary aims were to assess the utility of the surgical KPIs and make recommendations for future surgical trauma care review. Methods: Data on 22 surgical parameters were prospectively collected for 150 injured patients who had primary surgery at Camp Bastion between 1 May 2013 and 20 August 2013. Additional information for these patients was obtained using the Joint Theatre Trauma Register. The authors assessed data recording, applicability and compliance with the KPIs. Results: Median data recording was 100% (IQR 98%–100%), median applicability was 56% (IQR 10%–99%) and median compliance was 78% (IQR 58%–93%). One KPI was not applicable to any patient in our population. Eleven KPIs achieved >80% compliance, five KPIs had 80%–60% compliance and five KPIs had <60% compliance. Recommendations are made for minor modifications to the current KPIs. Conclusion: 78% compliance with the DMS KPIs provides a snapshot of the performance of the surgical aspect of military trauma care in 2013. The KPIs highlight areas for improvement in service delivery. Individual KPI development should be driven by evidence and reflect advances in practice and knowledge. A method of stakeholder consultation, and sequential refinement following evidence review, may be the right process to develop the future set of DMS KPIs.